C reactive protein and prealbumin as markers of disease activity in shigellosis. Issue 3 (September 1995) - Khan, W A; Salam, M A; Bennish, M L
Abstract : To evaluate serum C reactive protein (CRP) and prealbumin concentrations as markers of disease activity in shigellosis this study serially measured serum concentrations of CRP and prealbumin in 39 patients infected with Shigella spp, and a comparison group of 10 patients infected with Vibrio cholerae serotype 01. On admission, patients with shigellosis had significantly higher median concentrations of CRP (109 v 5 mg/l; p < 0.01) and significantly lower median concentrations of prealbumin (16 v 23 mg/l; p < 0.01) than did patient with cholera. Among Shigella spp infected patients, CRP concentrations were significantly lower, and prealbumin concentrations significantly higher, on study days 3 and 5 when compared with admission values. Among Shigella spp infected patients, those in whom treatment failed had higher admission CRP concentrations than those in whom treatment was successful (p = 0.142). An admission CRP concentration > or = 110 mg/l had a 70% sensitivity and a 61% specificity in predicting failure of treatment among patients infected with Shigella spp; the predictive value of a positive and negative test was 14% and 96% respectively. In summary, acute shigellosis elicits an acute phase response, the magnitude of which predicts clinical outcome.